Penatalaksanaan Fisioterapi pada Kasus Hernia Nucleus Pulposus Cervical 6-7 Di RS PKU Muhammadiyah Surakarta - Al Mahdi, Iqbal, Umi Budi Wahyuni (2016)
Background: Hernia Nucleus Pulposus (HNP) is evisceration nucleus from discus interventebralis so nucleus protruding to annulus fibrosus and gives manivestation of nerve compression that causes pain, limited range of motion, reduction muscle strength. Modality that can be used to address problems of physiotherapy in the case Hernia Nucleus Pulposus Cervical include Infra Red, Transcutaneus Electrical Nerve Stimulation (TENS), and McKenzie Cervical Exercise to reducing pain, increasing range of motion, and improve the muscle strength. Purpose: Detected physiotherapy management in reducing pain, increasing renge of motion, and increasing muscle strength in the case of Hernia Nucleus Pulposus Cervical 6-7 using modalities Infra Red, Transcutaneous Electrical Nerve Stimulation (TENS), and Mc. Kenzie Cervical Exercise. Result: After therapy for about six times the obtained results of increase pain, in silent pain T1 : 6,3 to T6 : 0, tenderness T1 : 7,5 to T6 : 2,5, motion pain T1 : 8,3 to T6 : 4,2. Increase range of motion in cervical flexi T1 : 5 cm to T6 : 0 cm, ekstensi T1 : 16 cm to T6 : 20 cm, Lateral fleksi sinistra T1 : 14 cm to T6 : 11 cm, rotasi sinistra T1 : 17 cm to T6 : 13 cm, increase range of motion in shoulder sagital T1 : S:45o-0o-110o to T6: S:45o-0o-180o, frontal T1 : F:100o-0o-30o to T6 : F:180o-0o-35o , rotasi T1 : R(F=90):55o-0o-50o to T1 : R(F=90):80o-0o-90o. increase muscle strength in cervical flexor neck T1: 3 to T6: 4, ekstensor neck T1: 3 to T6 4, lateral flexor neck sinistra T1: 3 to T6: 4, rotator neck sinistra T1: 3 to T6: 4, increase muscle strength in shoulder flexor shoulder T1 : 3 to T6 : 4, abductor shoulder T1 : 3 to T6 : 4. Conclusion: Infra Red, Transcutaneus Electrical Nerve Stimulation (TENS) and McKenzie Cervical Exercise can reduce pain, improve range of motion cervical and shoulder, and increase muscle strength in the case of Hernia Nucleus Pulposus Cervical.